Bones are forever [large type] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2012)
Forensic anthropologist Tempe Brennan examines the bodies of three babies while Detective Ryan investigates their mother in a case with ties to the high-stakes world of diamond mining.